STUDI PERBANDINGAN RENTABILITAS BANK SEBELUM DENGAN SETELAH PENERAPAN MANAJEMEN RISIKO - Sustika, Adi; Wiksuana, I Gusti Bagus (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.05.NO.02.TAHUN 2016, 2016)
Risk management is a set of method and procedures used to identify, measure, monitor, and control risk arising in all business of the bank. Risk management was first time implemented in the Bank Pembangunan Daerah Bali, in 2011. The application of risk management is an addition to measure, monitor, and control risk arising from all the business of the banks, which is also expected to improve the performance of organizational and increase the profitability of the bank itself.   This research was conducted at the Bank Pembangunan Daerah Bali, which the ratio of profitability studied are Return on Assets Ratio (ROA), Return on Equity (ROE), and Operating Expenses to Operating Income (BOPO) in the period prior to the application of risk management i.e. 2009 to by the year 2010, and the period after the implementation of risk management in 2012 to 2013 quarterly period. The methods of data analysis used are two different test methods on average, which the number of samples used as many as eight (8) pairs of data. The data of this study is a secondary data obtained from the financial statements and risk management at the Bank Pembangunan Daerah Bali. Results showed that: (1) There are significant differences relationship between ROA before and after the implementation of Risk Management. (2) There are significant differences between ROE before and after the implementation of Risk Management. (3) There are significant differences between BOPO before and after the implementation of Risk Management. Suggested to PT. Bank Pembangunan Daerah Bali to keep the implementation of risk management and continuously fix it to be better, because it significantly take effect especially to ROA and ROE.
Keywords: risk management,return on assets, return on equity,operating expenses to operating income